(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
In the present article the dependence of the use of 13 tense forms of the verb on two factors – type of texts and verb semantics – is analyzed. The obtained results show that past tenses are preferred in fiction, the Present Indefinite tense is preferred in scientific prose, while present and future tenses are preferred in journalistic texts. The dependence between verb semantics and the use of tenses is characterized by the intensity of connections between their grammatical and lexical meanings and the selectivity sense collocations. Various tenses of the verb have different degrees of the selectivity of compatibility with the semantic verb groups (subclasses).